Konsentrasi Dan Lama Perendaman Ekstrak Bawang Merah (Allium Cepa L.) Terhadap Invigorasi Benih Jagung ( Zea Mays L.) Kadarluasa - Windra Jayadi; Adnan; Rizky Septika Utami; Eko Fransisko (Fakultas Pertanian Universitas Ratu Samban, 2023)
Seeds that are expired will result in delays in the process of growth and germination. This study aims to determine the concentration of shallot extract on the growth of expired corn seeds, determine the soaking time of shallot extract on the growth of expired corn seeds and determine the best combination between the concentration and soaking time of expired shallot extract on the growth of expired corn seeds. This research was carried out in the Pat Petulai University laboratory from April 2021 to May 2021 in Curup. The seeds used are hybrid corn seeds Pioneer P32 which had expired on April 15, 2020. This study used a completely randomized design (CRD) factorial with 2 factors. The first factor is the concentration of shallot extract (K) consisting of 4 levels K0 = Without giving shallot extract (Control), K1 = Concentration of shallot extract 20% /100 ml distilled water, K2 = Concentration of shallot extract 40% /100 ml distilled water .K3 = Concentration of shallot extract 60%/ 100 ml of distilled water, while the second factor is soaking time (P) consisting of 4 levels: P0 = Without immersion (control) P1 = 3 hours P2 = 6 hours P3 = 9 hours. The observed variables included germination rate, sprout height, stem diameter, plant fresh weight. Data were analyzed using Analysis of Variance at 5% level. If there is a significant difference, it will be continued with the Least Significant Difference (LSD) test. The results showed that the treatment with shallot extract concentration and soaking time had a significant effect on plant height, stem diameter and plant fresh weight, but had no effect on sprout height and root length. It was found that there was an interaction between the concentration of shallot extract and the soaking time because it could increase the increase in plant height and plant wet weight. The best plant height, stem diameter and plant fresh weight were seen in the treatment of shallot extract concentration of 60%/100 m l of distilled water.